WUJUD DAN POLA PENALARAN NILAI KEPEDULIAN, KREATIF, DAN SOPAN SANTUN MATERI AJAR BAHASA INDONESIA DALAM BUKU SISWA KELAS VII KURIKULUM 2013 - Handayani, Liza Tri; Sabardila, Atiqa (Jurnal Penelitian Humaniora, 2017)
In the last a couple of years, national character has been degraded. In the field, data showed that the morality or character of the Indonesians has now collapsed. Character education through the learning process can be very helpful. In addition to the learning process, it turns out the learning material too. We often find that in the textbook, they contain learning materials to the value of the attitude that must be followed. The purpose of this study is to describe the nature and patterns of reasoning values of caring, creative, and manners in Indonesian learning materials in class VII curriculum 2013. This research uses descriptive explanative technique. The data of this study is learning materials of text containing the value of caring, creative, and manners. Data were analyzed using data flow model of Miles and Huberman. The results showed that there were 27 form values of caring, 11 creative values, and 6 manners values in Indonesian learning materials in books class VII curriculum 2013. It was also the pattern of reasoning appropriate at this stage of the scientific approach. The pattern of reasoning realized that the process of deductive reasoning, analogy inductive, deductive analogy, the relationship between causal phenomenon, due to the cause, and 1 causal-effect 2. The new pattern appears that the causal relationship 1-induced second-result 3, and causal relationship-effects.